The effects of climate change on cereals yield of production and food security in Gambia - Loum, Alieu; Fogarassy, Csaba (Applied Studies in Agribusiness and Commerce, 2015)
Increasingly, empirical evidences are substantiating the effects of climate change on agricultural production is a reality. In the early part of the 20th century many were skeptical about the so-called climate change that is due to global warming. The Intergovernmental Panel on Climate Change (IPCC, 2007) defines climate change as follows: “climate change refers to a change in the state of the climate that can be identified by changes in the mean or variability of its properties and that persists for extended periods, typically decades or longer” This study analyses the impact of climate change on cereals production (millet and maize) in the Gambia using a time series data for a period of 46 years (1960 – 2013) at an aggregate level to assess the relationship between climate (temperatures and rainfall,) and non-climate variables fertilizer, area planted respectively and yield. The specific objectives of the research are: (1) How climate change affects the expected cereals (Millet and Maize) output or yield in the Gambia. (2) How the level of output risk within cereals (Millet and Maize) farming is affected? In order to achieve these set objectives, the paper will adopt Just and Pope modified Ricardian production functions for climate change impact assessments (e.g., Chen et al. 2004), the paper will also control for the impacts of regular input factors in the production process. The study used a data set for the Gambia comprising variables relevant for cereals production and climate information from 1960 through 2013. There is strong evidence that climate will affects Maize and Millet; according to the analysis 77% and 44% of the variability in the yield of Maize and Millet respectively is explained by the climate and non-climate variables included in the model. Given the effects of climate variables on cereals production, and increasing climate change vulnerabilities on other food production section, the result of this paper will add voice to the growing call for policy makers to step up funding in research and development in climate change adaptation and mitigation.JEL classification: Q54